Determination of Thermophysical Properties and Fire Resistance of Wooden Structures - Davronovich, Amonov Daler; Nabievich, Ganiev Jakhongir; Murodjon, Aslanov; Sardor, Sarimsokov (European Journal of Life Safety and Stability (2660-9630), 2022)
The safety of buildings and structures built of wooden structures primarily depends on its fire resistance. To this end, the article will see some connections, it is advisable to conduct a comprehensive study of the thermophysical properties of wood, taking into account the influence of temperature and humidity factors. Recommendations are given for their use in the calculations of drying, wood impregnation and fire resistance of wooden structures